African systems of thought : studies presented and discussed at the third International African Seminar in Salisbury, December 1960 - International African Seminar. (3d. : 1960 : Salisbury, Southern Rhodesia) (Oxford University Press, 1965)
Bilingual symposium, French and English, raises many of the issues central to the emerging study of African systems of thought at that time, including the question of their systematicity and whether religion is identifiable as a discrete body of data.
free
Keywords: Africa – Religion – Congresses